R21, a novel particle based vaccine for a multi-component approach to malaria vaccination - Collins, K (2014)
Malaria is a major cause of mortality and morbidity and an effective vaccine is an urgent global health priority. This thesis evaluates the liver stage viral vector regimen ChAd63 – MVA ME.TRAP in humans and demonstrates the induction of partial protective efficacy (21%) against sporozoite challenge, mediated by high levels of antigen-specific T cells. Although this efficacy is suboptimal, the only subunit vaccine regimen found to elicit greater efficacy has been the particle vaccine, RTS,S/AS01B. This vaccine has been evaluated in large phase 3 trials in Africa and elicits between 30-50% efficacy, mediated predominantly by antibodies that target the circumsporozoite (CS) protein at the sporozoite stage of infection. The aim of this thesis is to enhance pre-erythrocytic stage subunit vaccine efficacy using two approaches. Firstly, by increasing the immunogenicity of a CS-based particle vaccine and secondly, by combining the particle vaccine with ChAd63 – MVA ME.TRAP. To enhance the immunogenicity of the CS-based particle an improved RTS,S like vaccine called R21 was developed. The major improvement is that the R21 particle is formed from a single CS-HBsAg fusion protein and contains a much higher percentage of CS antigen than RTS,S, which may lead to enhanced immunogenicity and efficacy. R21 was found to be immunogenic at a very low dose, used alone or in a range of adjuvants and elicited sterile efficacy when administered with ISCOM adjuvants. Concurrent induction of both cellular and humoral immunity was achieved by combining R21 with ChAd63 – MVA ME.TRAP and no immunological interference was seen. Furthermore, sterile efficacy against sporozoite challenge was significantly enhanced when R21 was administered with TRAP based viral vectors. These pre-clinical studies have provided important information for the selection of a suitable adjuvant and proof of concept that these vaccines can be combined. R21 is now being taken forward for evaluation in Phase 1/2a clinical trials with the future aim of combining it with the ChAd63 - MVA ME.TRAP regimen in humans.